Critical Success Factors in Integrating Sustainability with Quality: The Case of a Food and Beverage Company - Purcidonio, Paula Michelle; Marchi Lemos Grillo, Nicholas; de Castro Cruz Alarcão, Vinícius (Brazilian Journal of Operations & Production Management, 2020)
Goal: Analyzing critical success factors (CSFs) for integrating sustainability and quality in a food and beverage company in Rio de Janeiro, Brazil. Design/methodology/approach: This research relies on an exploratory method, applied on qualitative data collection based on a case study. The instrument for data collection is an interview with professionals who work in the areas of quality and sustainability in the company studied. Results: Out of the seven critical success factors identified in an organization, six of them (leadership and commitment to strategy, management and monitoring of processes, training and communication, commitment to the three pillars of sustainability, product/service development and continuous improvement) are a result of the company’s strategic circumstances, achieved by continuously improving products and processes. On the other hand, there is a critical focus factor for stakeholder relations, since it is currently very concentrated on the interests of final consumers to the detriment of other stakeholders. Limits of the investigation: Results reflect the Brazilian headquarters of a multinational company of the food and beverage sector and, therefore, cannot necessarily be applied to other companies of the same sector. Practical implications: Diagnosing seven critical success factors of the studied food and beverage company raises the opportunity to seek mechanisms to strengthen the focus on stakeholders, a critical factor identified as incipient in the research. Originality/value: Findings confirm the relevance of looking into the critical success factors identified by the literature about integrating sustainability and quality in the practice of industries.